Jurors on Trial: Lawyers Using the Internet to Research Prospective Jurors - O'Hagan, Lydia (Victoria University of Wellington Law Review, 2014)
This article examines a practice whereby lawyers use the internet to research prospective jurors with a view to challenge. It is unclear how common the practice is in New Zealand, but the increasing availability of personal information online means that lawyers have a plethora of personal information about prospective jurors at their fingertips. Currently peremptory challenges are exercised in a discriminatory fashion on the basis of broad stereotypes. It is argued that pretrial research by lawyers on prospective jurors could secure a more impartial jury by providing a mechanism for uncovering attitudinal biases or predispositions, meaning the challenges will be exercised on the basis of stereotypes alone less often. Pretrial research by lawyers could also remedy the disparity of resources between prosecution and defence by providing an independent vehicle for obtaining information. This article discusses the benefits of pretrial research of prospective jurors and argues that any drawbacks are limited. Potential guidelines for lawyers conducting pretrial research around the collection, use, retention and disclosure of information are proposed. This article concludes that pretrial research of prospective jurors serves to protect, rather than undermine, the fundamental right of all parties to a fair trial.